(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This paper’s goal is to present a revised guideline for data point numerical integration. This approach is based on computations of the harmonic and arithmetic means of the points that make up our interval to evaluate the precision of our approach. Numerous comparisons are computed. This procedure produces highly accurate results.